Pour une approche renouvelée de la psychologie de développement vocationnel - Bégino, Luc (Canadian Journal of Counselling and Psychotherapy, 2012)
This article describes how the cognitive system operates as a mediator through which personal and vocational organization is achieved by the individual. A model which specifies the domains relevant to vocational development is derived and discussed. Miller's (1956) discovery in the area of information processing is covered and its relative importance to the vocational theory stressed. Eleven propositions for a new approach of vocational development are exposed. Finally, two exploratory studies, based on this new theoretical approach as it applies to vocational information, were conducted. The purpose of the first study was to derive a scheme of data analysis. Four developmental behaviors were identified in this study. The purpose of the second study was to replicate the first study and improve upon the procedures. The four developmental behaviors were observed again and a fifth one described. Based on the information obtained in these twostudies, the author concludes that the new theory of vocational development as proposed has relevance.